Social Recognition in Invertebrates 2015
DOI: 10.1007/978-3-319-17599-7_10
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Nestmate Recognition in Social Hymenoptera

Abstract: The ability to discriminate between friends and foes is a central feature of social life. In social insects, nestmate recognition is mediated by colony specific cuticular hydrocarbons (CHCs) (label) that are perceived by an individual and compared with its neural representation of the colony odour (template). Although numerous advances have been made in understanding the identity, origin and production of recognition cues in social hymenoptera, relatively little is known about the ontogeny of nestmate recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 181 publications
(188 reference statements)
0
10
0
Order By: Relevance
“…On the contrary, small pre-emergence colonies show a higher heterogeneity, with wider variation in the physiological status of foundresses (Pardi, 1946(Pardi, , 1948Röseler et al, 1980;Röseler, 1991) and relatedness (Queller et al, 2000;Leadbeater et al, 2011), all factors that are known to affect CHC individual profile (Bonavita-Cougourdan et al, 1991;Sledge et al, 2001;Dapporto et al, 2004bDapporto et al, , 2005. The colonial chemical signature is the product of a template shared by all individuals thanks to social interactions (contacts, trophallaxis) and through the nest material (Signorotti et al, 2015). It is likely that the more homogeneous conditions of late-season colonies allow the production of a more marked and reliable colonial chemical signature, while in pre-emergence colonies, individual level heterogeneity might somehow reduce inter-colony differences in the chemical profile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, small pre-emergence colonies show a higher heterogeneity, with wider variation in the physiological status of foundresses (Pardi, 1946(Pardi, , 1948Röseler et al, 1980;Röseler, 1991) and relatedness (Queller et al, 2000;Leadbeater et al, 2011), all factors that are known to affect CHC individual profile (Bonavita-Cougourdan et al, 1991;Sledge et al, 2001;Dapporto et al, 2004bDapporto et al, , 2005. The colonial chemical signature is the product of a template shared by all individuals thanks to social interactions (contacts, trophallaxis) and through the nest material (Signorotti et al, 2015). It is likely that the more homogeneous conditions of late-season colonies allow the production of a more marked and reliable colonial chemical signature, while in pre-emergence colonies, individual level heterogeneity might somehow reduce inter-colony differences in the chemical profile.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that age (foundresses are several months old, while workers are only days/weeks old) or caste-related differences (foundresses are reproductive individuals while workers are not) could have played a role. While we believe that age is unlikely to have an influence, as Polistes wasps are able to perform NMR within a few hours after emergence (thus well before the time at which they were tested) (reviewed in Signorotti et al, 2015), we cannot discard the hypothesis of differences between castes in the NMR system as it has been shown in a social bee (Wittwer and Elgar, 2018). Previous studies offered mixed evidence for the related species Polistes fuscatus: one study documented differences in recognition between queens and workers (with queens having a more restrictive acceptance threshold than workers against unrelated conspecific intruders; Fishwild and Gamboa, 1992), while a more recent experiment found no evidence of such a queen-worker variation in recognition (with workers showing similar ability in familiar recognition compared to queens; Injaian and Tibbetts, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spiders, the expression of tolerant behaviors requires the processing of chemical information as evidenced, for example, in the wolf spider Geolycosa turricola where spiderlings with impaired chemoreception perform more aggression than do untreated individuals [61]. In the highly integrated colonies of ants, the social isolation of workers impairs nestmate recognition because of a partial loss of the internal template used to discriminate nestmates from non-nestmates [62,63]. Here, the analysis of the chemical signatures of spiderlings revealed similar profiles between spiderlings raised alone or in groups, which strongly suggested that social isolation influenced the processing, not the emission, of social cues.…”
Section: Discussionmentioning
confidence: 99%
“…A social group is usually a highly complex environment, which can change over time in both the composition and social role of their members, and recognition processes appear to be finely entwined with the social network of interactions that an individual experiences through its life [42,43]. Given the plasticity in the structure of many social environments [44][45][46], it may be evolutionarily advantageous that group members should reflect a certain degree of plasticity in their recognition system, with the ability to adjust or update their templates based on contextual contingencies [42,43,47]. For example, in many social insect species, the colony odour is dynamic and can change over time owing to multiple factors (i.e.…”
Section: Introduction (A) Understanding the Timing And Cues Of Social Recognitionmentioning
confidence: 99%